The Introduction of Earthen House (Part 1) - คำพุฒ ประชุม (Frontiers in Engineering Innovation Research, 2005)
The aim of introduction of earthen house is to collect the knowledge about earthen house in Thailand such as history of earthen house, problems, obstacles and advantages and disadvantages. In this research was found that the building of earthen house was popular and distributed in the group of eco-tourists and mostly that were the place of meditation and hill tribe’s accommodation. Moreover, that was extended to the eco-resorts business because the expenses of earthen house was cheaper than the normal house and the temperature in the house was comfortably. Therefor that was applied to be used as the accommodation for the poor people in the village and development to be used for saving energy in the future.